Ionospheric absorption of HF radio wave in vertical propagation - Unal, I.; Ozcan, O.; Canyilmaz, M. (Shiraz University, 2007)
In this study, absorption of high frequency radio waves in the ionospheric plasma have been investigated. The wave equation was obtained in terms of ionospheric parameters. The numerical values of the absorption have been calculated for 4 MHz, 4.5 MHz and 5 MHz waves. The necessary parameters for calculation have been obtained using an International Reference Ionosphere (IRI) Model. The altitudinal, diurnal, seasonal and the variations of absorption with frequency have been examined. The calculations show that the highest absorption occurs in the D-region. The absorption is higher in summer than in other seasons and is maximum at daylight. In addition, absorption decreases with the increase of frequency. © Shiraz University.
Keywords: Absorption; HF wave; Ionosphere